Investigasi Faktor yang Mempengaruhi Motivasi Kerja - Abdi Maliki; Hidayat (Asosiasi Ahli Administrasi Indonesia, 2020)
The purpose of this study is to find out the determinants to increase employees' motivation to work, as well as how much salary, informal communication, and organizational commitment affect employees' work motivation. This type of research is a survey. The total sample of the total population, namely 70 employees. Data are analyzed using multiple regression. The results of the study indicate that salary, informal communication, and organizational communication have an effect on increasing employees' work motivation. However, only organization commitment that influence work motivation partially.